ANALYTICAL TRANSFORMATIONS IN MINIMIZING LOGICAL FUNCTIONS - Kabulov, A.V.; Normatov, I.Kh.; Urunbaev, E.; Ashurov, A.O. (FAN va JAMIYAT, 2019)
The article is devoted to analytic transformations in minimizing logical functions in the class of disjunctive normal forms. Some analytical formulas for transforming logical expressions in a general form are derived. The problems of formation and transformation of various analytical expressions are solved, and the theorems of formulas representation and transformation in various bases of functions of logic algebra are proved.